Morphological integrity of individuals in plant populations of grass and subshrub layer - Коваленко, І. М. (Problems of Environmental Biotechnology, 2016)
The article deals with the integrity of plants of grass and subshrub layer in forest ecosystems of the north-east of Ukraine. More than 1000 individuals of eight plant species have been studied with the use of the morphological integration index. It has been found that the morphological integration index depends primarily on plant species. The lowest index was found in Calluna vulgaris (20,2), and the highest index – in Asarum europaeum (67,9). Morphogenetic integration of plant individuals varies significantly, depending on the age and density of stands.